The Concept of Language Environment: A Descriptive Study at Madrasah Aliah Keagamaan Gresik - Imam Nur Aziz; Yuli Ani Setyo Dewi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2019)
Learners’ success in acquiring a new language is very much affected and conditioned by the environment. The factor of environment establishes students’ interest and student motivation to improve students speaking skill. Even though English has been taught for at least six years in school levels in Indonesia, the students still have some difficulties in learning English whether it is the productive or receptive skill, especially speaking. the researcher conducted a research to answer the research questions. (1) How does the implementation of Language Environment on students’ speaking skill at Madrasah Aliah Keagamaan (Islamic Senior High/MAK) Mambaus Sholihin Gresik. (2) What are the accurate method, strategy and system to learn English at Madrasah Aliah Keagamaan (MAK) Mambaus Sholihin Gresik. The subject of the research was the students of MAK Mambaus Sholihin Gresik. There were 34 students’ in Elementary Level and 26 students’ in Intermediate level. The research used Ethnographic research and the techniques are Observation, Interview and Documentation. The factors of language environment are learning process and students activities, materials used based on students’ need, and intents guidedance.